2008
DOI: 10.1093/rpd/ncn144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exposure parameters in plain radiography: a comparative study with European guidelines

Abstract: Typical distribution of exposure parameters in plain radiography is unknown in Portugal. This study aims to identify exposure parameters that are being used in plain radiography in the Lisbon area and to compare the collected data with European references [Commission of European Communities (CEC) guidelines]. The results show that in four examinations (skull, chest, lumbar spine and pelvis), there is a strong tendency of using exposure times above the European recommendation. The X-ray tube potential values (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Specifically, at KKUH, the higher potential values and the lower current values allowed a considerable dose reduction without loss of image quality. Indeed, it has previously been reported that higher potential values allow considerable dose reduction without sacrificing image quality (Lanca et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, at KKUH, the higher potential values and the lower current values allowed a considerable dose reduction without loss of image quality. Indeed, it has previously been reported that higher potential values allow considerable dose reduction without sacrificing image quality (Lanca et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of implemented local/national recommendations may be another possible cause. In Portugal, a wide variability in patient dose values due to a lack of implemented local/national recommendations, as well as a lack of criteria for good radiographic techniques was reported (Lanca et al, 2008). Implementation of national references could achieve an ESD reduction of between 30 and 60% below the Commission of European Communities (CEC) recommendations (Vano et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the international literature many articles can be found describing digital detector systems and presenting comparisons among various systems with regard to their diagnostic performance [5][6][7][8][9]. The characteristics of the x-ray beam, especially the x-ray beam energy, can also contribute to image quality.…”
Section: Introductionmentioning
confidence: 99%